(untitled) (Mustansiria Dental Journal, 2018)
The mandibular canal appears below or superimposed over the apices of the mandibular molar teeth but it has some variations regarding its distance to both lower first molar and the base border of the mandible that may make a problem specially for the oral surgeon in his work during operations like implantation, so, this study was done to estimate the position of the mandibular canal and its relation to the lower first molar and the base border of the mandible by the aid of digital panoramic radiographs. The sample of this study was collected from patients who attended Al-Karama specialized center for dentistry. Forty patients were selected in this study with the age range between 20-60 years (males and females) that divided in to four groups according to a special criteria. Forty digital views (OPG) were taken for Iraqi patients, using computerized digital panoramic x-ray machine. All radiographs were examined and then the position of the mandibular canal for each patient was estimated. The results revealed that the mandibular canal is most commonly located away from the root apices of lower first molar, and the distance between the mandibular canal and the base border of the mandible is indirectly proportional with age.